pengaruh PENGARUH KUALITAS PRODUK, SALURAN DISTRIBUSI DAN KEPUASAN PELANGGAN TERHADAP LOYALITAS PELANGGAN PADA PT. FATONA JAYA SUKSES - Situmeang, Rosinta Romauli; ., Yuwanndy; ., Veronika; Yeohan, Cindy (2020)
The purpose of this study was to test and analyze the effect of product quality, distribution channels and customer satisfaction on customer loyalty , the decrease in customer loyalty is due to the inadequate product quality ,distribution channels and customer satisfaction . the theory used is related to product quality, distribution channels and customer satisfaction and customer loyalty . the population in this study amounted to 216 customer and a sample of 140 customers . the sampling technique used was random sampling. the data analysis used was validity and reliability test, classical assumption test , multiple linear regression analysis, hypotesis testing. the conclusion in this study is that partially and simultaneously product quality , distribution channels and customer satisfaction have a positive and significant effect on customer loyalty at PT Fatona Jaya Sukses